Integration of Eye-Tracking Technology in Virtual Reality Applications for Basketball Training: A Mixed Methods Needs Assessment - Ahmad Rahmadani; Oki Candra; Feby Elra Perdima; Syed Kamaruzaman Syed Ali; Joseph T Lobo; Novri Gazali (CV. FOUNDAE, 2025)
Background: The integration of virtual reality (VR) and eye-tracking (ET) technologies has considerable potential for enhancing perceptual–cognitive skill development in basketball. However, existing research provides limited guidance on the technical and pedagogical requirements for designing VR–ET systems that are both instructionally meaningful and aligned with user needs. Aims: This study aims to identify these key design requirements through a user-centred mixed-methods approach. Methods: Semi-structured interviews and focus group discussions with coaches and lecturers were conducted to explore training challenges, expectations, and pedagogical considerations. Insights from the qualitative phase informed the development of a questionnaire administered to student-athletes (N = 120), allowing for the validation and prioritisation of system requirements. Qualitative data were analysed thematically, while quantitative data were examined using descriptive statistics. Result: The integrated findings reveal six essential domains for effective VR–ET system design: immersive tactical–technical visualisation, interactive decision-making scenarios, gaze-based performance indicators, real-time visual feedback, learning support features, and implementation readiness. Users emphasised the value of VR–ET for enhancing tactical understanding, attentional control, and personalised training experiences. Conclusion: This study contributes both theoretically and methodologically by addressing the lack of user-informed frameworks in VR–ET research and demonstrating the value of participatory mixed-methods approaches in sports technology development. The results provide a foundational design blueprint for future VR–ET prototypes and offer new insights into how immersive and gaze-based technologies can support athlete learning in team sports.